2014
DOI: 10.1159/000368228
|View full text |Cite
|
Sign up to set email alerts
|

Onset and Phoneme Awareness and Its Relationship to Letter Knowledge in German-Speaking Preschool Children

Abstract: Objectives: The aim was to explore whether word-initial onset awareness is acquired before phoneme awareness and whether onset complexity influences performance on identification tasks. In addition, the relationship between onset and phoneme awareness and letter knowledge was investigated. Method: In this study, 22 monolingual German-speaking preschool children aged 5;00-5;11 were tested. Onset, phoneme identification, and letter knowledge tasks were administered. The children were presented with pictures of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Second, children within the same age group did not behave all in the same way but instead exhibited substantial individual variability (Figure 2), a phenomenon also previously noted (e.g., review in Sosa and Stoel-Gammon, 2012; see also Wimmer and Mayringer, 2002;Schäfer et al, 2014). In the present study, this was the case in all three age groups and for all assessments, except for tasks probing phonemic awareness in kindergarteners (onset segments, phoneme synthesis) for which we noted a floor effect.…”
Section: Age-related Versus Skill-based Descriptions Of Spoken Languasupporting
confidence: 80%
See 1 more Smart Citation
“…Second, children within the same age group did not behave all in the same way but instead exhibited substantial individual variability (Figure 2), a phenomenon also previously noted (e.g., review in Sosa and Stoel-Gammon, 2012; see also Wimmer and Mayringer, 2002;Schäfer et al, 2014). In the present study, this was the case in all three age groups and for all assessments, except for tasks probing phonemic awareness in kindergarteners (onset segments, phoneme synthesis) for which we noted a floor effect.…”
Section: Age-related Versus Skill-based Descriptions Of Spoken Languasupporting
confidence: 80%
“…In the past decade, a fair amount of empirical research has reported greater vocabulary and phonological awareness in school-aged children than children in kindergarten (in German: Kauschke, 2000;Wimmer and Mayringer, 2002;Schäfer et al, 2014;in English: Carroll et al, 2003;Ziegler and Goswami, 2005). However, results from the present study suggest that age-driven categorizations are not always the only suitable ways to characterize skill development or at least they may underestimate its complexity.…”
Section: Age-related Versus Skill-based Descriptions Of Spoken Languamentioning
confidence: 99%
“…In learning, the child is stimulated to think about the phoneme-grapheme correspondences, the relation between written language and spoken language, and about orthographic patterns, establishing a higher phonemic awareness (8) . There are several studies in the literature (1,4,6,(8)(9)(10) involving the phonological awareness skills and children in the literacy period.…”
Section: Introductionmentioning
confidence: 99%